Quantification of atropine sulphate monohydrate and obidoxime dichloride in two‐chamber autoinjectors for accessing uniformity of dosage. Issue 11 (12th November 2022) - Spreitzer, Iva; Morawej, Paniz; Wosolsobe, Richard; Stinzl, Rainer; Wackerlig, Judith
Abstract: In the treatment of organophosphate poisoning atropine sulphate monohydrate (AT) and obidoxime dichloride (OB) play a vital role. Currently, the Austrian Armed Forces use the DOUBLEPEN OA two‐chamber autoinjector (ChemProtect) to administer these two drugs. The autoinjector is a part of military standard equipment as a "Basic CBRN‐First Aid Kit" and contains OB and AT with a declared concentration of 220 mg/2 ml and 2 mg/2 ml, respectively. Especially in the two‐chamber autoinjectors, it is highly possible that not all the content of the antidote solution is administered when the autoinjector is triggered. The purpose of the study was to analyze one hundred DOUBLEPEN OA autoinjectors from two different production batches (1707068 and 1707067) for volume loss, drug content and uniformity of dosage unit. Uniformity of dosage units, assessed by the content uniformity method (Chapter 2.9.40 of the European Pharmacopeia), requires the calculation of an acceptable value to quantify the uniformity of the drug product. An acceptance value for the first 10 dosage units of 15.0% or below is considered acceptable. The loss of volume was calculated by determining the density and mass of the solution after triggering the autoinjector. A quantitative high‐performance liquid chromatography method has been developed and in‐house validated for the determination of the content of two drugs. According to International Council for Harmonisation guidelines, the analytical method was proven to be accurate and repeatable. The obtained results show that the average loss of volume after injection was 5%, and the average content of OB and AT for batch 1707068, was 216.5 and 1.9 mg, while for batch 1707067 it was 224.2 and 2.0 mg, respectively. Although the loss of volume and content were observed, the calculated acceptance value for both production batches met the requirements of uniformity of dosage unit by the European Pharmacopeia.